Pattern of newborn babies delivered by cesarean section - Guslihan D Tjipta; Riza I Nasution; Dachrul Aldy; Zakaria Siregar (Indonesian Pediatric Society Publishing House, 2016)
Background The birth rate in Indonesia is still high and abnormal labor constitutes 15% of all deliveries which needs cesarean sec- tion as a solution for complicated cases. Objectives To find the general physical condition of babies born after cesarean section as well as the characteristics of mothers who underwent cesarean section. Methods A retrospective study on newborn babies delivered by cesarean section conducted in Subdivision of Neonatology, Medi- cal School, University of North Sumatera-Pirngadi Hospital Medan, in period of 2 years (1991-1992). Results There were 8762 babies born during the study period, 1484 babies (16.93%) delivered by cesarean section due to pla- centa previa (26.2%), prolonged labor (15.8%), cephalopelvic dis- proportion (10.3%), neglected labor (9.9%), eclampsia/preeclamp- sia (8.1%), fetal distress (7.5%), previous section (6.6%), breech presentation (5.7%), solutio placenta (4.0%), and others (5.9%). It was shown that mothers undergoing caesarean section was mainly 20-30 years old (66.4%), multigravida (47.8%), term gestational age (79.4%), and minimal antenatal care (61.3%). There were 1224 (82.5%) babies with birth weight >2500 grams and 894 (60.2%) suffered from asphyxia. Conclusions The evidence of asphyxia by cesarean section and low birth weight group was significantly different from those nor- mally delivered (p<0.001). The mortality rate was 11.5% due to still birth 29.2%, RDS 18.3%, sepsis 15.5%, pneumonia 12.3%, and gastroenteritis 11.5%